Pengaruh Literasi Keuangan, Sikap Keuangan, dan Gaya Hidup Terhadap Pengelolaan Keuangan Pribadi Mahasiswa Perguruan Tinggi - Fayzia Laif; Adrie Putra (Economic Reviews Journal, 2024)
This study aims to analyze the influence of financial literacy, financial attitudes, and lifestyle on personal financial management among university students in West Jakarta. Using a quantitative associative causal approach, primary data were collected through an online questionnaire with a Likert scale. The data analysis methods included descriptive statistics, data quality tests, classical assumption tests, multiple linear regression, and hypothesis testing. The results of the study indicate that simultaneously, financial literacy, financial attitudes, and lifestyle have a significant influence on personal financial management among students. However, partial analysis reveals that only financial attitudes and lifestyle have a positive and significant impact, while financial literacy does not show a significant influence on personal financial management.